2015
DOI: 10.1007/s10847-015-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of computational models of β-cyclodextrin complexes: structural studies of morniflumate hydrochloride and β-cyclodextrin complex in aqueous solution by quantitative ROESY analysis

Abstract: Complexation of morniflumate hydrochloride (MOR) with b-cyclodextrin (b-CD) in aqueous solution was studied. Structure of the MOR-b-CD inclusion complex was obtained by a combination of 1 H NMR and molecular modeling studies. Computational models obtained by molecular mechanics and molecular dynamics were analyzed for their atom-accuracy. ROESY crosspeak intensities calculated from intermolecular interproton distances were compared with experimental intensities. The results demonstrate that comparison of calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…To unambiguously confirm the encapsulation, ROESY is the preferred NMR tool. ROESY studies have been extensively used to get information on inclusion complexes with βCD through analysis of intermolecular peaks between cavity protons and a part of the guest involved in complexation. ,, ,, Figure shows representative ROESY spectra obtained for the sample ChU/βCD/H 2 O/AN and ChU/βCD/H 2 O/Tol. The host–guest interactions are displayed as intermolecular correlation peaks between aromatic protons of AN and Tol and protons H 3′ and H 5′ of βCD.…”
Section: Resultsmentioning
confidence: 99%
“…To unambiguously confirm the encapsulation, ROESY is the preferred NMR tool. ROESY studies have been extensively used to get information on inclusion complexes with βCD through analysis of intermolecular peaks between cavity protons and a part of the guest involved in complexation. ,, ,, Figure shows representative ROESY spectra obtained for the sample ChU/βCD/H 2 O/AN and ChU/βCD/H 2 O/Tol. The host–guest interactions are displayed as intermolecular correlation peaks between aromatic protons of AN and Tol and protons H 3′ and H 5′ of βCD.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the intermolecular proton distances obtained from quantum chemical calculations are shown in Table . A major point to be noted here is that in the case of supramolecular complexes, the internuclear distance between the host and guest is measured mostly by employing NOE-based experiments, viz., ROESY , for intermediate-sized molecules. In the present study, we have demonstrated that by selecting a pair of nuclei, one hailing from the host molecule and one from the guest molecule, and measuring the bi-selective relaxation rates, one can evaluate the internuclear distance using prior knowledge of the molecular rotational correlation time of the encapsulated species.…”
Section: Resultsmentioning
confidence: 99%
“…The chemical formulas for quercetin (QUR) (PubChem ID: 5280343), linalool (LIN) (PubChem ID: 6549), and the standard drug diazepam (DZP) (PubChem ID: 3016) ( Figure 1 ) were taken from the PubChem chemical database in the ‘sdf’ file format. The Allinger’s force field (MM2) method was used for energy minimization of the ligands by Chem3D Pro21.0 software [ 108 ].…”
Section: Methodsmentioning
confidence: 99%